Resistant starch and protein intake enhances fat oxidation and feelings of fullness in lean and overweight/obese women. Issue 1 (December 2015) - Gentile, Christopher; Ward, Emery; Holst, Jens; Astrup, Arne; Ormsbee, Michael; Connelly, Scott; Arciero, Paul
Abstract Background Diets high in either resistant starch or protein have been shown to aid in weight management. We examined the effects of meals high in non-resistant or resistant starch with and without elevated protein intake on substrate utilization, energy expenditure, and satiety in lean and overweight/obese women. Methods Women of varying levels of adiposity consumed one of four pancake test meals in a single-blind, randomized crossover design: 1) waxy maize (control) starch (WMS); 2) waxy maize starch and whey protein (WMS+WP); 3) resistant starch (RS); or 4) RS and whey protein (RS+WP). Results Total post-prandial energy expenditure did not differ following any of the four test meals (WMS = 197.9 ± 8.9; WMS+WP = 188 ± 8.1; RS = 191.9 ± 8.9; RS+WP = 195.8 ± 8.7, kcals/180 min), although the combination of RS+WP, but not either intervention alone, significantly increased (P <0.01) fat oxidation (WMS = 89.5 ± 5.4; WMS+WP = 84.5 ± 7.2; RS = 97.4 ± 5.4; RS+WP = 107.8 ± 5.4, kcals/180 min). Measures of fullness increased (125 % vs. 45 %) and hunger decreased (55 % vs. 16 %) following WP supplemented versus non-whey conditions (WMS+WP, RS+WP vs. WMS, RS), whereas circulating hunger and satiety factors were not different among any of the test meals. However, peptide YY (PYY) was significantly elevated at 180 min following RS+WP meal. Conclusions The combined consumption of dietary resistant starch and protein increases fat oxidation, PYY, and enhances feelings of satiety and fullness to levels that may be clinically relevant if maintained under chronic conditions. This trial was registered at clinicaltrials.gov as NCT02418429.